A critical discourse analysis of sexuality education in the Australian curriculum. Issue 5 (3rd September 2019) - Ezer, Paulina; Jones, Tiffany; Fisher, Christopher; Power, Jennifer
ABSTRACT: This article examines the sexuality education component of the national Australian Curriculum: Health and Physical Education (AC:HPE) with a focus on sexuality education discourses. A critical discourse analysis explored official AC:HPE documents in relation to sexuality education; the sexuality education discourses present within these documents; teacher roles and expectations associated with each discourse; and Australia's broader social context in relation to education. Findings reveal that the AC:HPE emphasises a teacher-facilitated approach to sexuality education, which contrasts with teacher-centred work dominating the field prior to its release. This approach is in line with recent shifts in education towards strengths-based learning in which students are encouraged to think critically about issues. Despite these emphases, and while the AC:HPE is meant to be used flexibly as a guideline or framework, certain ambiguities within it may leave teachers' roles open to interpretation and practices therefore unchanged or undisputed.